Tools and Algorithms for the Construction and Analysis of Systems 25 Years of TACAS: TOOLympics, Held as Part of ETAPS 2019, Prague, Czech Republic, April 6-11, 2019, Proceedings, Part III - Beyer, Dirk; Huisman, Marieke; Kordon, Fabrice; Steffen, Bernhard (Lecture Notes in Computer Science, 2019)
This book is Open Access under a CC BY licence. This book, LNCS 11429, is part III of the proceedings of the 25th International Conference on Tools and Algorithms for the Construction and Analysis of Systems, TACAS 2019, which took place in Prague, Czech Republic, in April 2019, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2019. It's a special volume on the occasion of the 25 year anniversary of TACAS.